Revolutionizing Development Reflections on the Work of Robert Chambers - Cornwall, Andrea; Scoones, Ian (Taylor & Francis, 2022)
This book tells the story of development studies in practice over the last fifty years through the work of one remarkable individual, Robert Chambers. His work has taken him from being a colonial officer in Kenya through training and managing large rural development projects to a fundamental critique of top-down development and the championing of participatory approaches. The contributors eloquently demonstrate how he has been at the centre of major shifts in development thinking and practice over this period, popularising terms that are now at the centre of the development lexicon such as vulnerability, multi-dimensional poverty, sustainable livelihoods and 'farmer first'. Robert Chambers played a major role in the massive growth in participatory approaches to development, and particularly the application of participatory methods in development research and appraisal. This has led to fundamental challenges to development practice, ranging from approaches to monitoring and evaluation to institutional learning and professional training. There is probably no-one who has had more influence on approaches to development in the past decades. Revolutionizing Development offers a unique overview of these contributions in thirty-two concise chapters from authors who have been intimately involved as collaborators, critics and colleagues of Robert Chambers.